2017
DOI: 10.2172/1410224
|View full text |Cite
|
Sign up to set email alerts
|

Special Purpose Nuclear Reactor (5 MW) for Reliable Power at Remote Sites Assessment Report

Abstract: The Phenomena Identification and Ranking Table (PIRT) technique was conducted on the Special Purpose Reactor nuclear plant design. The PIRT is a structured process to identify safety-relevant/safety-significant phenomena and assess the importance and knowledge base by ranking the phenomena. The Special Purpose Reactor is currently in the conceptual design phase. The candidate reactor has a solid monolithic stainless steel core with an array of heat pipes and fuel pellets embedded in the monolith. The heat pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Publicly available data for the expected neutron flux or fluence to which microreactor components would be exposed are more limited. Sterbentz et al reports a fast flux at the core midplane of 5.5 × 10 13 n/cm 2 /s for a heat pipe-cooled microreactor [14]. For constant operation times of 1, 5, and 20 years, this would correspond to fast neutron fluences of 1.73 × 10 21 , 8.67 × 10 21 , and 3.47 × 10 22 n/cm 2 , respectively.…”
Section: Microreactor Sensing Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publicly available data for the expected neutron flux or fluence to which microreactor components would be exposed are more limited. Sterbentz et al reports a fast flux at the core midplane of 5.5 × 10 13 n/cm 2 /s for a heat pipe-cooled microreactor [14]. For constant operation times of 1, 5, and 20 years, this would correspond to fast neutron fluences of 1.73 × 10 21 , 8.67 × 10 21 , and 3.47 × 10 22 n/cm 2 , respectively.…”
Section: Microreactor Sensing Requirementsmentioning
confidence: 99%
“…Sterbentz et al analyzed three different 5 MWth heat pipe-cooled designs and reported maximum heat-pipe wall temperatures of 712.5, 677, and 712.5 • C for each of these designs [14,15]. Therefore, for heat pipe-based microreactors that integrate heat pipes within monolithic metal structures, acoustic sensors would be required to survive temperatures up to 800-900 • C to provide data regarding the structural health of the monolithic core block.…”
Section: Microreactor Sensing Requirementsmentioning
confidence: 99%
“…• Manufacturing of the monolith core: The LANL MegaPower design calls for a stainless steel monolith to house the heat pipes and fuel. In a 2017 Phenomena Identification and Ranking Table (PIRT) analysis of the MegaPower concept by INL, the manufacturability of the steel monolith was identified as a significant issue [37]. Hot isostatic press (HIP), 3D printing or other advanced manufacturing processes may yield a path forward on monolith manufacturability.…”
Section: Heat Pipe Cooled Reactormentioning
confidence: 99%
“…The INL PIRT analysis conducted for the LANL MegaPower reactor examined the power conversion system in some detail [37]. The report examined an air Brayton cycle due to its wide use in power conversion systems, and therefore the wide availability of components.…”
Section: Open Air Brayton Cyclementioning
confidence: 99%
“…8, 9, and 10), culminating in a successful test of a kilowatt-scale space reactor 2,3 and a conceptual design of a megawattscale design. 11 These early successes have led to an interest in the commercial sector for terrestrial and offworld applications.…”
Section: Introductionmentioning
confidence: 99%